Clinical Predictors of Pain Relief with 60-Day Peripheral Nerve Stimulation: A Multicenter Observational Study - Odonkor CA; Oghenesume O; Hirani S; Bohacek S; Gutierrez DE; Sekhar R; McCormick ZL; Poree L; Abd-Elsayed A (Journal of Pain Research)
Charles A Odonkor,1 Oghenewoma Oghenesume,2 Salman Hirani,3 Siri Bohacek,3 David E Gutierrez,4 Rajat Sekhar,5 Zachary L McCormick,6 Lawrence Poree,7 Alaa Abd-Elsayed8 1Department of Orthopaedics and Rehabilitation, Division of Physiatry, Interventional Pain Medicine, Yale School of Medicine, Yale New Haven Hospital, New Haven, CT, USA; 2Yale University School of Medicine, New Haven, CT, USA; 3Department of Anesthesiology and Perioperative Medicine, Division of Pain Medicine, Oregon Health & Science University, Portland, OR, USA; 4Hartford Healthcare Medical Group Division of Physical Medicine & Rehabilitation, University of Connecticut School of Medicine, Hartford, CT, USA; 5Hartford Healthcare Medical Group Division of Pain Medicine, Ayers Neuroscience Institute, Hartford, CT, USA; 6Department of Physical Medicine and Rehabilitation, University of Utah School of Medicine, Salt Lake City, UT, USA; 7Department of Anesthesia, University of California, San Francisco, CA, USA; 8Department of Anesthesiology, University of Wisconsin, Madison, WI, USACorrespondence: Charles A Odonkor, Department of Orthopaedics and Rehabilitation, Division of Physiatry, Interventional Pain Medicine, Yale University School of Medicine, 47 College Street, New Haven, CT, 06510, USA, Email kcodonkor@aya.yale.eduBackground: Clinical predictors of pain relief with 60-day peripheral nerve stimulation (PNS) remained undefined. Identifying the factors associated with treatment outcomes may improve patient selection and optimize results.Objective: This study examined baseline physical activity, pain, disability, and psychological factors influencing early versus delayed response and non-response to a 60-day PNS.Methods: A prospective, multicenter, observational cohort study was conducted on 73 patients who consecutively received a 60-day PNS. Baseline assessments included pain (numeric rating scale [NRS]), disability (Oswestry Disability Index [ODI]), psychological profiles (Pain Self-Efficacy Questionnaire, PSEQ; Pain Catastrophizing Scale, PCS), and physical activity (physical activity vital signs [PAVS]). Logistic regression and principal component analysis were used to identify the predictors of response phenotypes.Results: Early (≥ 50% pain relief within 7– 14 days of PNS implant that is sustained through the entire 60-day period) and delayed (< 50% pain relief in the first 14 days but eventually reaching ≥ 50% before the end of the 60 days) responder rates were 26% and 43%, respectively. Non-responders (< 50% pain relief at the end of the 60-day treatment period) comprised 30.1% of the group. Predictors of early response included high physical activity (OR=4.22, p=0.0006, Area Under the Curve [AUC] =0.81), high pain self-efficacy (OR=1.12, p=0.0004, AUC=0.86), and low catastrophizing (OR=0.88, p=0.0003, AUC=0.86). A delayed response was associated with a longer chronic pain duration (OR=0.83, p=0.027) and high baseline ODI (OR=0.43, p=0.002; AUC=0.79). Nonresponse was linked to psychological distress (eigenvalue =3.23, 40.3% variance), opioid dependency, and morbid obesity (eigenvalue =1.63, 20.4% variance).Conclusion: This real-world study showed that baseline physical activity, psychological resilience, and pain behaviors predicted response to a 60-day PNS. Non-responders presented with psychological distress, morbid obesity, and opioid dependence. These findings may refine patient selection and help to set treatment expectations for 60-day PNS.Plain Language Summary: Peripheral nerve stimulation (PNS) is a promising therapy for chronic pain. However, it is difficult to predict which patients will benefit the most. This study examined patient characteristics that influence response (early and delayed) or nonresponse to 60-day PNS treatment.Patients from multiple health systems completed surveys before treatment to assess pain levels, physical activity, disability, and psychological factors. Our research team analyzed medical records to identify predictors of successful response and nonresponse to a 60-day PNS treatment.The results showed that:Early responders (patients who benefited quickly) had higher physical activity levels, greater confidence in managing pain (pain self-efficacy), and lower pain-related distress (catastrophizing).Delayed responders (patients who improved gradually) had longer histories of chronic pain and more severe baseline pain disability.Non-responders (patients who did not experience significant pain relief) tended to exhibit higher psychological distress, opioid dependence, and morbid obesity.These findings suggest that baseline physical activity, psychological coping, and behavioral factors could help to identify ideal candidates for PNS therapy. Understanding these predictors may improve patient selection, treatment expectations, and long-term pain management strategies.Keywords: physical activity, neuromodulation, 60-day PNS, pain catastrophizing, self-efficacy, morbid obesity